Change in the meiofauna community structure of sandy beaches of the nuevo gulf (Chubut, Argentina) - Harguinteguy, Carlos Alfredo (2012)
The composition and distribution of the benthic meiofauna assemblages of the Nuevo Gulf (Chubut, Argentina) are described in relation to abiotic variables. The meiofauna and sediment samples were collected in the intertidal zone of four sandy beaches with different anthropic disturbances in June 2005. The samples were obtained at 20 sampling sites using a 2.5 cm diameter core tube at a depth of 10 cm. A total of 13 meiofauna taxa were identified, with the meiofauna being primarily represented by nematodes, gastrotrichs, ciliates and polychaetes and the meiofauna abundances ranging from 1.5 × 103 to 6.5 × 103 ind. 10 cm-2. Univariate (one-way ANOVA test) and multivariate (ANOSIM/MDS test) analyses showed clear dissimilarities in community structures between sites with anthropic effects and those in pristine condition, revealed by the significant differences were found between beaches near to and far away from a city with port activity. The meiofaunal assemblage varied in abundance and diversity, and these changes in the community structure may have been related to environmental gradients on the shore. The BIO-ENV analysis showed that the redox potential discontinuity depth might be the main factor in the spatial distribution of organisms.